Comparative analysis of frameworks using TypeScript to build server applications - Golec, Marcin; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2022)
The subject of the research was a comparative analysis of programming frameworks that are intended for building applications. NestJS (version 8.1.1), FoalTS (version 2.5.0) and Ts.ED (version 6.69.1) were put together. An experiment was prepared based on scenarios that focused on the response time of applications to requests. Each of them had the same set of functionalities. NestJS turned out to be the most efficient of the compared skeletons. It achieved the best results. The worst results in each scenario were achieved by Ts.ED, especially with higher loads. The biggest differences in the comparison can be seen in studies conducted according to a scenario based on GET-type requests, and in particular with more objects in response.